Kriteria Kepemimpinan dalam Al-Qur’an: Analisis Q.S. Al-Anbiya Ayat 73, Q.S. As-Sajdah Ayat 24, dan Q.S. Yusuf Ayat 55 (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
Leadership is a fundamental aspect of human life that greatly determines the direction and quality of a society. The Qur’an, as the primary source of Islamic teachings, provides clear guidance regarding the criteria of an ideal leader based on divine values. This study aims to examine leadership criteria in the Qur’an through an analysis of Q.S. Al-Anbiya verse 73, Q.S. As-Sajdah verse 24, and Q.S. Yusuf verse 55. The research employs a library research method by analyzing the lexical meanings (mufradat), the historical context of the verses, and the interpretations of prominent mufassirs such as Buya Hamka and Muhammad Quraish Shihab. The findings indicate that leadership from a Qur’anic perspective is not merely oriented toward power, but is a great trust (amanah) that requires moral and spiritual integrity, patience, faith, trustworthiness, and competence. These verses emphasize that an ideal leader is one who guides others according to Allah’s command, possesses patience and strong conviction in His revelations, and is knowledgeable and trustworthy in managing public affairs. This study is relevant to contemporary conditions, particularly in addressing the leadership crisis marked by the abuse of power and weakened integrity. Therefore, understanding leadership criteria in the Qur’an is expected to serve as a foundation for Muslims in selecting and preparing leaders who are ethical, responsible, and morally upright.